Factors Affecting External Audit Fee: A Survey of Mining Sector Companies in Indonesia - Nazara, Arizaro; Rusmanto, Toto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this research is to examine the effect of Profitability, Company Complexity, Audit Committee, Public Accounting Firm Size, Company Risk, and Company Size on External Audit Fees. The sample used in this study was 23 mining companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2020. The sampling technique used was the purposive sampling method. The secondary data in this study is based on the Annual Report published on the IDX official website and the official website of the sample companies. Hypothesis testing in this study uses multiple linear regression analysis with the help of IBM SPSS 26 software and a significant level of 5%. The results of this study indicate that (1) Profitability has no effect on External Audit Fees, (2) Company Complexity has a significant positive effect on External Audit Fees, (3) Audit Committee has no effect on External Audit Fees, (4) Public Accounting Firm size has a significant positive effect. On External Audit Fees, (5) Company risk does not affect External Audit Fees, and (6) Company size has a significant positive effect on External Audit Fees.